Pandangan Nasionalisme - Theofilus Welem (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Gus Dur or Abdurahman Wahid is a national figure who is often referred to as the father of Pluralism due to his open attitude towards the existence of other religions in his life's journey, especially when he led as President. This paper provides an explanation of Gus Dur's views on nationalism and religious life in Indonesia. The research method used is a qualitative research method. The conclusion of this paper is that in the view of